2013
DOI: 10.1016/j.bbr.2013.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Males, but not females, lose tyrosine hydroxylase fibers in the medial prefrontal cortex and are impaired on a delayed alternation task during aging

Abstract: The structure of the prefrontal cortex (PFC) is particularly vulnerable to the effects of aging, and behaviors mediated by the PFC are impaired during aging in both humans and animals. In male rats, behavioral deficits have been correlated with a decrease in dopaminergic functioning. However, studies have found that anatomical changes associated with aging are sexually dimorphic, with males experiencing greater age-related loss than females. The present study investigated the effects of sex and aging on perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Contrary to our hypothesis, the analysis of females at P35 and males at P45 suggested that the pubertal onset was not accompanied by changes in THir fiber volume in either sex. This would seemingly conflict with previous studies documenting both long and short‐term effects of gonadal hormones on TH expression in the PFC during early development (King et al, ; Kritzer, ; Willing & Wagner, ), young adulthood (Kritzer & Kohama, ; Kritzer et al, ) and in aged rats (Chisholm et al, ; Chisholm, Packard, Koss, & Juraska, ). Depending upon the presence of specific receptors, steroid hormone actions could have different or even contrasting effects during different periods of development.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…Contrary to our hypothesis, the analysis of females at P35 and males at P45 suggested that the pubertal onset was not accompanied by changes in THir fiber volume in either sex. This would seemingly conflict with previous studies documenting both long and short‐term effects of gonadal hormones on TH expression in the PFC during early development (King et al, ; Kritzer, ; Willing & Wagner, ), young adulthood (Kritzer & Kohama, ; Kritzer et al, ) and in aged rats (Chisholm et al, ; Chisholm, Packard, Koss, & Juraska, ). Depending upon the presence of specific receptors, steroid hormone actions could have different or even contrasting effects during different periods of development.…”
Section: Discussionmentioning
confidence: 63%
“…For each section, bilateral images were taken from layer 1, layers 2/3, and layers 5/6. Identification of these PFC subregions and cortical layers was made possible by their proximity to adjacent white matter under the frontal cortex and THir fiber orientation as was discussed in previous work from our laboratory (Chisholm, Kim, & Juraska, ). Briefly, layer 1 is comprised of a dense band of fibers with a dorsal/ventral orientation, fibers in layers 2/3 are arranged in a medial to lateral direction, while the fibers in 5/6 do not have a clear orientation (Figure ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…10 ). The same pattern of differences occurred in the density of tyrosine hydroxylase throughout the layers of the mPFC, so that males had more density as adults while females had a higher density during aging ( Chisholm et al 2013 ). Again, it should be noted that the aging females in all of these studies were secreting moderate to low levels of estrogen and progesterone.…”
Section: Sex Differences In Aging: Structure and Behaviormentioning
confidence: 86%